Dialogic Argumentation as a Vehicle for Developing Young Adolescents’ Thinking - Kuhn, Deanna; Crowell, Amanda (Psychological Science, 2011)
Argumentive reasoning skills are featured in the new K–12 Common Standards (Common Core State Standards Initiative, 2010), yet with little said about their nature or how to instill them. Distinguishing reasoning skills from writing skills, we report on a multiyear intervention that used electronically conducted dialogues on social issues as the medium to develop argumentive reasoning skills in two cohorts of young adolescents. Intervention groups demonstrated transfer of the dialogic activity to two individual essays on new topics; argument quality for these groups exceeded that of comparison groups who participated in an intervention involving the more face-valid activity of extensive essay writing practice, along with whole-class discussion. The intervention group also demonstrated greater awareness of the relevance of evidence to argument. The dialogic method thus appears to be a viable one for developing cognitive skills that the comparison-group data show do not routinely develop during this age period.